Innovative history education exemplar activities - Leeuw-Roord, Joke van der; Köksal, Hüseyin (Harf, 2012)
Innovative History Teaching – Exemplar Lessons, which includes 34 lessons. All lessons are connected to different curriculum topics, as well learning outcomes. They are categorised in four categories: (1) Multiperspectivity, (2) Controversial Issues, (3) Critical Thinking and (4) Creative Thinking. In addition, all topics have as well a strong element of making history be the history of ordinary people’s every-day lives. These 34 lesson modules are all based on referenced sources as evidence, and work towards a deeper students understanding of multiperspectivity. This material was developed over the course of three years, involving over 170 History Educators from all regions of Turkey. It was developed during the EUROCLIO/Matra Project A Key to Europe - Innovative Methodology in Turkish School History.